Design Pembelajaran Online Berbasis Authentik Bagi Siswa Sekolah - Abna Hidayati; Vevi Sunarti; Reza Gusmanti (Jurnal Dedikasi Pendidikan, 2023)
This study is focused on issues with online learning, such as a lack of authentic activities completed by students, which resulted in poor levels of accomplishment in cognitive and psychomotor components. The goal of the study is to find online learning activities for elementary school pupils that combine an authentic learning approach with real-world activities. Quasy Experiment is a sort of quantitative research involving a pretest and posttest research design. A total of 14 elementary school pupils were included in the investigation. In this study, the tool is a test sheet. To find an independent sample test, the data is processed using the SPSS application. The results demonstrated that utilizing online learning designs with realistic and real-world activities resulted in an increase in learning activities and outcomes. Learning with an online learning design that incorporates authentic and real-world activities differs greatly from traditional learning. Based on these circumstances, it is advised that teachers use a variety of realistic activities in online learning to develop elementary school students' knowledge and skills